Understanding the Nature of CSR Partnerships in Egypt - EL Nenaei, Menna (AUC Knowledge Fountain, 2021)
The field of Corporate Social Responsibility (CSR) has seen considerable growth in Egypt over the past decade, especially in the field of sustainable development. A growing number of Egyptian private companies are actively taking responsibility for Egypt’s environment and social development by investing in CSR activities. Egyptian private sector-based CSR activities are expected to further increase as corporate spending designated for CSR activities continuous to grow. The outcomes of these CSR activities are affected by the partnerships present among the main stakeholders involved. To date the nature of these partnerships, especially with regard to how they are formed, their implementation and outcomes have barely been explored. This thesis fills this research gap by exploring the nature of CSR partnerships amongst two important stakeholders; the private sector and NPOs in Egypt. The research employs a qualitative research methodology based on semi-structured interviews. Interviews were carried out with Cairo-based companies active in financing CSR projects, non- profit organizations (Non-Governmental Organizations (NGOs) and International Organizations) who partner with corporates to execute CSR activities, governmental entities, and CSR experts. The findings indicate that agreement on the CSR strategy among participating stakeholders and clear identification of roles are two of the key success factors for a partnership. Another major finding of the study is that social media plays a vital role in creating partnership connections and in showcasing CSR partnership impacts. Furthermore, there is a sense amongst corporates and NPOs that the government needs to work more collaboratively with NPOs.